2018
DOI: 10.1186/s12967-018-1430-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of atorvastatin in suppressing tumor growth of uterine fibroids

Abstract: BackgroundMedical therapeutic options remain quite limited for uterine fibroids treatment. Statins, competitive inhibitors of 3-hydroxy-3-methylglutaryl-coenzyme A reductase, have anti-tumoral effects on multiple cancer types, however, little is known about their effects on uterine fibroids.MethodsInitially, we conducted a retrospective study of 120 patients with uterine fibroids and hyperlipidemia from the Second Affiliated Hospital of Wenzhou Medical University. Then, we evaluated the effect of atorvastatin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
1
7
1
Order By: Relevance
“…In contrast to our finding, Shen et al & Chen et al reported that atorvastatin treatment increases caspase‐3 levels [68,69]. Chen et al [68] demonstrated that atorvastatin significantly inhibited growth and induced apoptosis in human prostate cancer cells by inhibition of caspase‐3 activity.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our finding, Shen et al & Chen et al reported that atorvastatin treatment increases caspase‐3 levels [68,69]. Chen et al [68] demonstrated that atorvastatin significantly inhibited growth and induced apoptosis in human prostate cancer cells by inhibition of caspase‐3 activity.…”
Section: Discussioncontrasting
confidence: 99%
“…Chen et al [68] demonstrated that atorvastatin significantly inhibited growth and induced apoptosis in human prostate cancer cells by inhibition of caspase‐3 activity. Also, Shen et al [69] suggested that atorvastatin exerted anti‐tumor effects on uterine fibroids through induction of apoptosis in HMG‐CoA‐dependent pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Myalgia is the most common adverse reaction of atorvastatin [16]. Recent studies have suggested that atorvastatin also had anti-tumor properties and these studies have mainly focused on a relationship between cholesterol biosynthesis and cancer [17]. Some plausible mechanism for atorvastatin against cancer have also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover GGPP, a downstream lipid isoprenoid intermediate significantly rescued the effects of atorvastatin and claimed the 1st clinical as well as preclinical data on use of atorvastatin as a promising nonsurgical method for treating uterine fibroids. 11 As per Bjorkhem-Bergman et al, 12 there was a large difference between the statin concentrations used in cells in vitro experiments and those found in human plasma. They reported pharmacokinetic data that 40mg of simvastatin produces a mean serum concentration of 2.2-4.3nM and the highest concentration of 19-31nM, although its pleiotropic effect is examined in vitro using micromolar concentrations.…”
Section: Short Communicationmentioning
confidence: 93%